Global Stock Markets in the Twentieth Century - Jorion, Philippe; Goetzmann, William N. (Journal of Finance, 1999)
Abstract Long‐term estimates of expected return on equities are typically derived from U.S. data only. There are reasons to suspect that these estimates are subject to survivorship, as the United States is arguably the most successful capitalist system in the world. We collect a database of capital appreciation indexes for 39 markets going back to the 1920s. For 1921 to 1996, U.S. equities had the highest real return of all countries, at 4.3 percent, versus a median of 0.8 percent for other countries. The high equity premium obtained for U.S. equities appears to be the exception rather than the rule.